2021
DOI: 10.3390/socsci10080311
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coparenting on Mothers’ COVID-19-Related Stressors

Abstract: To test and explore whether more positive coparenting will significantly predict lower COVID-19-related stress across family configurations and dynamics and across both higher- and lower-income mothers, we developed and circulated an online survey among mothers from the U.S. and Canada. Coparenting was measured using the Coparenting Across Family Structures (CoPAFS) short form (27 items) scale, comprised of factors representing five coparenting dimensions: communication, respect, trust, animosity, and valuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previous studies have demonstrated that social support, particularly family support, protects individuals' mental health both directly and as a buffer for pandemic-related stress (Brown et al, 2020 ; Li and Xu, 2022 ; Szkody et al, 2021 ). Some studies also indicated that more supportive co-parenting is associated with less parental stress ( Giannotti et al, 2021 ; Lucassen et al, 2021 ; Pruett et al, 2021 ). The present study further demonstrated that family support and co-parenting work on parents' mental health both directly and indirectly, by attenuating daily parenting hassles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that social support, particularly family support, protects individuals' mental health both directly and as a buffer for pandemic-related stress (Brown et al, 2020 ; Li and Xu, 2022 ; Szkody et al, 2021 ). Some studies also indicated that more supportive co-parenting is associated with less parental stress ( Giannotti et al, 2021 ; Lucassen et al, 2021 ; Pruett et al, 2021 ). The present study further demonstrated that family support and co-parenting work on parents' mental health both directly and indirectly, by attenuating daily parenting hassles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the adverse effects on parenting stress and mental health, home confinement during the COVID-19 pandemic may have also offered a good opportunity to enhance the interaction between family members and their children ( Tang et al, 2021 ). Emerging evidence has shown that some family aspects, such as family support and co-parenting, are important protective factors against parenting stress and supporting mental health during lockdown ( Giannotti et al, 2021 ; Khoury et al, 2021 ; McRae et al, 2021 ; Pruett et al, 2021 ). During home confinement, family members become the most available resources for people to cope with the disrupted daily life routine ( Li and Xu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the lockdown period in Italy, coparenting support was associated with lower levels of parental stress ( Giannotti et al, 2021 ). Coparenting support was also associated with less COVID-19-related stress among mothers in North America ( Pruett et al., 2021 ). Additionally, another study found cooperative coparenting mitigated the effects of parental stress on harsh parenting during the lockdown in New Zealand ( McRae et al., 2021 ).…”
Section: Risk and Protective Factors Associated With Parental Burnoutmentioning
confidence: 99%
“…Although paternal involvement in household care and childcare has increased, studies show that mothers worldwide remain responsible for a significantly higher proportion of total household care and childcare (Craig & Mullan, 2011 ; McMunn et al, 2017 ; Paquette, 2004 ). Moreover, the COVID-19 pandemic further negatively impacted the distribution of childcare, with the burden falling on mothers, especially those with young children (Calarco et al, 2021 ; Pruett et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars argue that, unfortunately, COVID-19 pandemic-related disruptions, including school and childcare closures, some job losses, the shift to remote work, the implementation of social distancing, and the negotiation of different COVID-19 protocols among households further negatively impacted mothers disproportionately; making them responsible for additional childcare, especially those with young children (Calarco et al, 2021 ; Pruett et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%